Effect of a Misidentified Centre of a Type ASG Material Measure on the Determined Topographic Spatial Resolution of an Optical Point Sensor - Schaude, Janik; Gröschl, Andreas Christian; Hausotte, Tino (Metrology, 2022)
The article presents the determination of the topographic spatial resolution of an optical point sensor. It is quantified by the lateral period limit DLIM measured on a type ASG material measure, also called (topographic) Siemens star, with a confocal sensor following both a radial measurement and evaluation, as proposed by ISO 25178-70, and the measurement and subsequent evaluation of two line scans, proposed by the NPL Good Practice Guide. As will be shown, for the latter, an only slightly misidentified target centre of the Siemens star leads to quite significant errors of the determined DLIM. Remarkably, a misidentified target centre does not necessarily result in an overestimation of DLIM, but lower values might also be obtained. Therefore, a modified Good Practice Guide is proposed to determine DLIM more accurately, as it includes a thorough determination of the centre of the Siemens star as well. While the measurement and evaluation effort is increased slightly compared to the NPL Good Practice Guide, it is still much faster than a complete radial measurement and evaluation.
Keywords: surface metrology; topographic spatial resolution; lateral period limit; type ASG material measure; Siemens star; confocal sensor; nano measuring machine